Uji Farmakologis Ekstrak Kental Daun Meniran(Phyllanthus niruri Linn) Untuk Membantu Penyembuhan Luka Sayat Pada Tikus Putih Jantan (Rattus norvegicus strain Sprague-Dawley). - Herson Cahaya Himawan; Pramono; Dwi Ayu Resti (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2017)
People often use medicinal plants as an alternative to healing the wound. Injuries are often experienced by the human body either intentionally or unintentionally. The cut is a wound caused by an incision of a sharp object, wood and so on. One of the herbs that is often used as a traditional drug therapy is a meniran leaf that can help wound healing. The aim of this research is to know the effect of thick leaf extract of meniran (Phyllanthus niruri Linn) in accelerating the healing time of the wound on Sprague-Dawley male white rat. Gravy leaf extract was obtained from infusa process with water solvent at temperature below 60oC for 15 minutes. This test was made by 6 groups with negative control (wound left), positive control (given betadine) and given the thickness of leaves leaves concentrate 25%, 50%, 75% and 100%. Meniran leaf-thick extract wastopicallyadministered in four concentrations of 25%, 50%, 75% and 100%, extracted with sterile gauze with 2 cm deep cuts and 0.2 cm depth on the lower rats. The results showed that from each treatment the concentration has the ability to heal the wound, but has different values. The conclusions of this study were the fastest meniran leaf extracts for healing wounds in Sprague-Dawley Sprague-white male rats were concentrations of 100% and 75%.